2015
DOI: 10.15341/jbe(2155-7950)/03.06.2015/010
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Trust — A Systematic Literature Review

Abstract: Abstract:The role of trust has long been acknowledged among economists and political scientists. It is often argued that high levels of trust among people help promote democratization, economic activity, well-performing institutions and low levels of violence. Social media has been identified as a significant vehicle in fostering social connections however the depth and significance of these connections to the creation of trust has not been well developed. According to Robert Putnam trust derives from reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
1
18
1
Order By: Relevance
“…In this study, the element of trust as reported by participants referred to perception that a person and information shared by a person in Facebook can be trusted. This is consistent with previous study that reported low rating of trust through interaction in Facebook (Håkansson & Witmer, 2015). This can be attributed to Facebook interaction which lacks in non-verbal cues and thus enhance suspicious of human.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the element of trust as reported by participants referred to perception that a person and information shared by a person in Facebook can be trusted. This is consistent with previous study that reported low rating of trust through interaction in Facebook (Håkansson & Witmer, 2015). This can be attributed to Facebook interaction which lacks in non-verbal cues and thus enhance suspicious of human.…”
Section: Discussionsupporting
confidence: 93%
“…The consequence for digital social media is that, trust level is reduced or lost all together. The above views are contrary to the assertion of Hakansson (2015) who believed that digital social media affects trust positively because information is shared easily and at a lower cost than in personal interactions especially advertising and reaching out to customers. The central idea to him is communication.…”
Section: Understanding Trust and Social Mediacontrasting
confidence: 57%
“…•Trust (3): It is possible to say that high levels of trust provide democratization, economical stabilization, good performance, and productivity in the societies. Trust can be defined as an ethical value that is learned in the family in the early ages, and it requires mutual cooperation (Hakansson & Witmer, 2015). The subject of trust on media is evaluated as a subject that is being discussed especially in the last years directed towards the developments of new media and social media usage.…”
Section: Methodsmentioning
confidence: 99%